POLITICAL CULTURAL AND ANTI-CULTURAL OF UKRAINIAN SOCIETY - Довбня, О.М.; Довбня, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Considered the linkages between low level of political culture of the population, as well as of the ruling circles of Ukraine, and uncivilized political participation in decision of critical questions of national development. Examines the impact of immaturity of civil society and a sense of citizenship on formation of the negative forms of political activity.